Anonymous aggregator election protocol for wireless sensor networks - Shuai FU; Jian-feng MA; Hong-tao LI; GQi JIAN (Tongxin xuebao)
An anonymous cluster head election protocol in clustered wireless sensor networks was proposed.The protocol detailed the decision rules and mode of cluster construction while an anonymous veto protocol based on bilinear pairings was adopted to verify election results,ensuring the successful election of cluster heads.A corresponding anonymous data aggregation scheme was designed,through which data aggregation can be accomplished without revealing the identities of aggregators.Extensive analysis and simulation results show that the proposed protocol achieves anonymity,energy efficiency and security of cluster heads election simultaneously and can resist eavesdropping attacks,node compromise attacks and collusion attacks effectively.